2020
DOI: 10.1111/dom.13984
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and cardiorenal outcomes in diabetes: A reappraisal

Abstract: The guidance issued to the pharmaceutical industry by the US Food and Drug Administration in 2008 has led to the publication of a series of randomized, controlled cardiovascular outcomes trials with newer therapeutic classes of glucose-lowering medications. Several of these trials, which evaluated the newer therapeutic classes of sodium-glucose co-transporter-2 inhibitors and glucagon-like peptide-1 receptor agonists, have reported a reduced incidence of major adverse cardiovascular and/or renal outcomes, usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 72 publications
(88 reference statements)
0
45
0
Order By: Relevance
“…This hypothesis was corroborated by the ORIGIN study which showed that reduction in blood glucose levels per se did not reduce cardiovascular events in the studied population ( 30 ). However, as mentioned previously, the randomized data on metformin treatment in patients with documented cardiovascular disease are scarce and there is a definite need for more randomized data ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was corroborated by the ORIGIN study which showed that reduction in blood glucose levels per se did not reduce cardiovascular events in the studied population ( 30 ). However, as mentioned previously, the randomized data on metformin treatment in patients with documented cardiovascular disease are scarce and there is a definite need for more randomized data ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is partly because the metformin substudy of the UKPDS trial compared conventional therapy with metformin in 753 patients in a nested study design and that few patients were on randomized therapy after 5 years. ( 8 , 9 ) and there has been no randomized outcome trials to assess the effect of metformin on cardiovascular events. Furthermore, and most importantly, the recent large randomized clinical trials of sodium glucose co-transporter 2 (SGLT2)-inhibitors ( 10 ) and glucagon like peptide 1 (GLP1)-analogues ( 11 ) have provided strong evidence of a beneficial clinical effect of these newer drug classes.…”
mentioning
confidence: 99%
“…One main criticism is that UKPDS only comprised of individuals with a new diagnosis of T2D not based on a tight criteria (fasting blood glucose range from 6.1 to 15.0 mmol/L) who were not at particularly high risk of CVD in the first place [26]. It is important to remember that the inclusion of obese individuals in UKPDS is consistent with general T2D population and is more representative of the current diabetes population.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…The history of CVOTs can broadly be categorised into pre-2008 and post-2008 periods after the US Food and Drug Administration (FDA) introduced the new guidelines for cardiovascular evaluation of GLTs largely focussed around the composite end-point of Major Adverse Cardiovascular Events (MACE) following the discovery of increased adverse cardiovascular events associated with rosiglitazone use [38,39]. Hence, considerable caution is required when comparing older and newer trials, which are more standardised in design and amenable to meta-analysis [26]. It is also worth noting that the modern CVOTs are relatively short trials recruiting mostly high-risk individuals who are unrepresentative of the general population.…”
Section: Ukpds Vs Newer Cardiovascular Outcome Trials (Cvots)mentioning
confidence: 99%
See 1 more Smart Citation